INTEGRATING DISRUPTIVE INNOVATION, COMPETITIVE ADVANTAGE, AND BUSINESS NETWORKING CAPABILITY ON SMALL BUSINESS PERFORMANCE IN INDONESIA - Setyawati, Sri Murni; Rosiana, Monica; Adawiyah, Wiwiek Rabiatul (Faculty of Economics and Business Universitas Jenderal Soedirman, 2019)
This study aimed at explaining the influence of disruptive innovation on business performance with competitive advantage as a mediator and networking capability as moderate. The tool of analysis used was Structural Equation Modelling (SEM). The sample size of this research was 120 owners and/or managers of Small and Medium Enterprises (SMEs) in Purwokerto areas. The result showed that disruptive innovation has a positive effect on both business performance and competitive advantage. The study supported the view that competitive advantage has a positive impact on business performance.  Also, competitive advantage act as mediating variable on the relationship between disruptive innovation and business performance. Finally, the last hypothesis stated that networking as moderation variable of disruptive innovation to business performance was supported.